Flat Rental Housing in Medan Labuhan - Devin Defriza Harisdani; Edward Anugrah Zai (Talenta Publisher, 2018)
The slum is one of the problems in Medan Labuhan area that is difficult to avoid. One of the causes of a slum settlement in this region is due to the increasingly expensive and limited land that causes low-income people do not have enough purchasing power to live in better areas. In response to this situation, the development of a flat rental housing as called as Rusunawa is one alternative that can be done to meet the needs of the community. With the implementation of the Green Architecture concept, the planned Rental Flat Housing can use the maximum use of natural resources and reduce the negative impact on the environment and can create an effective, comfortable and livable dwelling in Medan Labuhan area.